Electromagnetic Characteristics of the Simplest Strip System - Koshovy, G. I. (Видавничий дім «Академперіодика», 2013)
The main electromagnetic characteristics of the noncoplanar system of two narrow strips with parallel edges are investigated. They are determined on the basis of the integral equation technique, using the local coordinate systems. Analytical expressions of the longitudinal and transverse surface current densities are presented. They are validated by passing to the limit of a single strip and allow both analytic and numerical examination of the strip interaction. By using the obtained expressions, the field in the far zone, the scattering cross section and the scattering coefficient are deduced. These expressions are sufficiently simple and convenient for numerical calculation.